Quantitative morphometric changes in vascular mild cognitive impairment patients: early diagnosis of dementia. (12th January 2023) - Guan, Jitian; Li, Qiuyu; Dai, Zhuozhi; Lai, Lingfeng; Sun, Shuyi; Geng, Yiqun; Shen, Zhiwei; Luo, Lan; Jia, Yanlong; Yang, Lin; Tang, Yanyan; Yan, Gen; et al.
Abstract: Vascular mild cognitive impairment (VMCI) is an early and reversible stage of dementia. Volume differences in regional gray matter may reveal the development and prognosis of VMCI. This study selected 2 of the most common types of VMCI, namely, periventricular white matter hyperintensities (PWMH, n  = 14) and strategic single infarctions (SSI, n  = 10), and used the voxel-based morphometry method to quantify their morphological characteristics. Meanwhile, age- and sex-matched healthy volunteers were included ( n  = 16). All the participants were neuropsychologically tested to characterize their cognitive function and underwent whole-brain magnetic resonance imaging scanning. Our results showed that the volumes of the bilateral temporal lobes and bilateral frontal gray matter were obviously diminished in the PWMH group. The atrophy volume difference was 4, 086 voxels in the left temporal lobe, 4, 154 voxels in the right temporal lobe, 1, 718 voxels in the left frontal lobe, and 1, 141 voxels in the right frontal lobe ( P  ≤ 0.001). Moreover, the characteristics of the gray matter atrophy associated with the PWMH were more similar to those associated with Alzheimer's disease than SSI, which further revealed the susceptibility for escalation from PWMH to dementia. In conclusion, PWMH patients and SSI patients have different morphological characteristics, which explain the different prognoses of VMCI.